If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -4 = -2x + 23 Reorder the terms: -4 + 3x = -2x + 23 Reorder the terms: -4 + 3x = 23 + -2x Solving -4 + 3x = 23 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -4 + 3x + 2x = 23 + -2x + 2x Combine like terms: 3x + 2x = 5x -4 + 5x = 23 + -2x + 2x Combine like terms: -2x + 2x = 0 -4 + 5x = 23 + 0 -4 + 5x = 23 Add '4' to each side of the equation. -4 + 4 + 5x = 23 + 4 Combine like terms: -4 + 4 = 0 0 + 5x = 23 + 4 5x = 23 + 4 Combine like terms: 23 + 4 = 27 5x = 27 Divide each side by '5'. x = 5.4 Simplifying x = 5.4
| 8x-2=5x+8 | | 5y-13=-7y+37 | | -5x+2=4x+11 | | 27=3+7+y+7 | | 16+2y=64 | | y=1.7*12+89 | | (-4x)/(x+7)-(8)/(x+7) | | 5x-4+4x+3x+6=38 | | 2w=4 | | b(2)+24=8 | | m+9=-34 | | 15x-4+9x+3+12x+5=40 | | 15x-4+9x+3+12x+5=40 | | 95.8=1.7x+89 | | m+9=34 | | 24+4h=10 | | 5(m-2)=-15 | | -3r-33=-9r+27 | | 3(3n+4)=54+6 | | 5x-x+1=0 | | 40+4x=34+6x | | 4r+7=3r+15 | | 93=6x+21 | | x/4/5=35 | | 48/6-(1+2) | | 83=43+8x | | y=1.7*4+89 | | n/5=-30 | | 63=5x+8 | | y/(-8)=8 | | x+2/(5x-15)*(10x^2-25x-15) | | y-27=27 |